Comparative Analysis of Average Annual Returns: A Study of Sensex (India) versus S&P/ASX 200 (Australia) and Nikkei 225 (Japan) - Bhattacharya, Dr. Sumona; Tiwari, Sushma (The journal of contemporary issues in business and government, 2023)
This research paper aims to compare the average annual returns of the Sensex (India) with two major stock market indices, namely the S&P/ASX 200 (Australia) and the Nikkei 225 (Japan). The objective is to analyze the performance of the Indian stock market in relation to these two international indices and determine the level of correlation or divergence between them. The study utilizes historical data of average annual returns from a specified time period (not provided) for the Sensex, S&P/ASX 200, and Nikkei 225. The research employs statistical analysis techniques such as mean calculation and comparison to measure and contrast the performance of the three indices. The primary focus is on determining whether the Sensex exhibits similar trends or diverges significantly from the S&P/ASX 200 and Nikkei 225. By examining the average annual returns, investors and researchers can gain valuable insights into the comparative performance and potential investment opportunities of the Indian stock market in relation to the Australian and Japanese markets. The findings of this research paper contribute to a better understanding of the global market dynamics and may assist investors in making informed decisions while diversifying their portfolios.